The First Moderns. Hotels overlooking the sea - Cunha Matos, Madalena, Patrícia, Marta, Raquel Santos Pedrosa, Sequeira, Costa Rêga (2008)
The First Moderns. Hotels overlooking the sea [Intervenção apresentada no Congresso Selling or Telling? Paradoxes in Tourism, Culture and Heritage, com Patrícia Santos Pedrosa]. ATLAS (Association for Tourism and Leisure Education), University of Brighton, Inglaterra